Detection of abscisic acid and relative transcript abundance in Syntrichia caninervis Mitt. (2nd October 2021) - Zhang, Yigong; Mutailifu, Ayibaiheremu; Zhang, Yi; Yang, Honglan; Zhang, Daoyuan
ABSTRACT: Introduction: Abscisic acid (ABA) is a plant hormone known to regulate environmental stress responses in various species. Endogenous ABA has been detected in only a limited number of bryophyte species. Methods: Samples of the desiccation-tolerant moss Syntrichia caninervis Mitt. were analysed by ultra-performance liquid chromatography–mass spectrometry to determine the endogenous ABA content of the gametophores. Quantitative real-time PCR was conducted to investigate the transcript abundance of ABA-related genes ( ZEP, NCED3, SnRK2, ABI1 and ABI5 ) during dehydration and rehydration and in response to exogenous ABA and cold stress. Key results: Over a 24 h period of dehydration, the mean ABA concentration of the gametophores ranged from 7.96 to 30.87 ng/g dry weight, being maximal at 6 h. The expression of ABA-related genes changed in response to abiotic stress. Conclusions: The results show that Syntrichia caninervis can generate ABA and suggest that ABA has crucial functions in the stress responses of this species. Our findings establish a foundation for further research on the physiological roles of ABA in S. caninervis and help extend our understanding of the biosynthetic, metabolic and signalling pathways of ABA in bryophytes.